Peran Pemerintah PERAN PEMERINTAH DESA DALAM MENDISTRIBUSIKAN BANTUAN LANGSUNG TUNAI (BLT) PADA MASA PANDEMI COVID 19 - Ansar, Muh; Usman, Jaelan; Wahid, Nur (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out the role of the village government in implementing the Direct Cash Assistance Program in an effort to handle COVID-19 in Uluway Village, Mengkendek District, Tana Toraja Regency. The research method used a qualitative description. Sources of data used primary data sources and secondary data with a total of 4 informants. The results of the study showed that the role of the government as a regulator in Uluway Village, Mengkendek District, Tana Toraja Regency was the village government issues a certificate for the formation of Covid 19 Volunteers. The government's role as a dynamist in Uluway Village, Mengkendek District, Tana Toraja Regency was to invite community leaders to participate in determining prospective beneficiaries of the assistance. Direct Cash (BLT) for Village Funds. The role of the government as a facilitator of Uluway Village, Mengkendek District, Tana Toraja Regency was to provide the community with the best service, the Uluway Village government prepared a forum for the community to submit complaints and aspirations.